Educational Aspects of Training of Pedagogical Staff for School Education in Podillya Province (1864-1917): Historiographical Dimension - Nadija Balabust (Pedagogical Discourse, 2012)
Based on historical and educational literature, archival materials and publications of periodicals the article analyzes unfamiliar educational aspects of teachers training for schools in Podillya province in the second half of the nineteenth century - early twentieth century in scientific works of domestic and foreign researchers